Strategi Politeknik Negeri Jakarta untuk Meningkatkan Akreditasi dan Reputasi Internasional - Tri Widjatmaka; Nur Hasyim; Zainal Nur Arifin; Nedsal Sixpria (Politeknik Negeri Jakarta, 2022)
This article describes the strategies of Politeknik Negeri Jakarta to increase its accreditation and international reputation. Its material is from the qualitative research results entitled Politeknik Negeri Jakarta strategy to accreditation dan international reputation increasing. The research problem is the strategy of the Politeknik Negeri Jakarta in increasing accreditation and Increasing International Reputation is not yet known so the purpose of the research is to describe the strategies of Politeknik Negeri Jakarta in increasing accreditation and international reputation. The data collected by participant observation and documentation study, while data analysis used qualitative analysis: domain analysis, taxonomy analysis, componential analysis, and finding cultural themes. The main findings are (i) its policies to become international reputation and accreditation, among others: increasing the study program accreditation on national and international standards, increasing the PNJ rating at the international level, and increasing the number of the international network, (ii) its programs, inter alia: increasing of quality of study programs, monitoring the quality assurance on study programs, and increasing the quality of the international network. The conclusion is that Politeknik Negeri Jakarta has made various efforts in order to become an international polytechnic.